The role of glycerophospholipid metabolism in feline parvovirus infected CRFK cells - Sun, Zhen; Zhu, Hongwei; Liu, Yang; Zhang, Jianlong; Jiang, Linlin; Yu, Xin; Yu, Jiayu; Zhang, Xingxiao (Frontiers in Microbiology, 2025)
BackgroundFeline panleukopenia, caused by the highly lethal feline parvovirus (FPV), lacks effective prevention and treatment strategies. This study aimed to elucidate the key metabolic regulatory mechanisms during FPV infection.MethodsCRFK cells were infected with the FPV013 strain. Viral identification was performed via cytopathic effect (CPE) observation, transmission electron microscopy (TEM), PCR, and VP2 protein detection using Western blot and immunofluorescence. Untargeted metabolomics analyzed metabolic changes at 12 h, 24 h, and 48 h post-infection (hpi). Key pathways were validated through enzyme activity inhibition (Meclizine targeting PCYT2) and gene silencing (siRNA targeting PLPP1 and LPIN3).ResultsMetabolomics revealed the most significant differences at 48 hpi, identifying six significantly altered glycerophospholipid metabolites. Inhibiting PCYT2 enzyme activity significantly reduced viral load (p < 0.01). Silencing either phospholipid phosphatase 1 (PLPP1) or LPIN3 significantly inhibited FPV replication, with IF staining showing reduced VP2 expression (p < 0.01). In contrast, blocking fatty acid synthesis (TOFA/C75 treatment) had no significant effect.ConclusionFPV infection promotes replication by reprogramming host cell glycerophospholipid metabolism. The PCYT2-mediated PE/PC synthesis pathway and the PLPP1 or LPIN3 regulated diacylglycerol (DG) generation pathway play central roles. This finding highlights the pivotal role of glycerophospholipid metabolism during FPV infection, offering insights into antiviral strategies targeting this pathway.